2016
DOI: 10.4236/oji.2016.62006
|View full text |Cite
|
Sign up to set email alerts
|

Isoforskolin from Native Plant <i>Coleus forskohlii</i> of Yunnan, China Plays Multiple Biological Roles

Abstract: Isoforskolin (ISOF) was isolated from Coleus forskohlii native to Yunnan in China. It is identified as one analog of diterpene forskolin (FSK) which comes from the Indian plant Coleus forskohlii. Researches found that the Yunnan native plant Coleus forskohlii contained rich ISOF but not FSK. ISOF was reported to activate adenylyl cyclase (AC) isoforms. The ophthalmologic and cardiovascular effects of ISOF were firstly reported in the 1990s. The researchers in Kunming, China, found ISOF could lower blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The plant Coleus forskohlii ( C. forskohlii ) is primarily distributed in India, Thailand, China, Egypt and Brazil, and has a history of use in the treatment of multiple diseases, including heart disease, respiratory disorders, convulsion, intestinal disturbance and liver fatigue ( 6 ). Isoforskolin (ISOF) is the principle active component of C. forskohlii native to the southwest region of China, and has previously been studied for its anti-inflammatory effects ( 7 , 8 ). Notably, a study performed by Yang et al ( 9 ) observed that ISOF reduced the secretion of lipopolysaccharide (LPS)-induced cytokines, namely TNF-α, IL-1β, IL-6 and IL-8, in human mononuclear leukocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The plant Coleus forskohlii ( C. forskohlii ) is primarily distributed in India, Thailand, China, Egypt and Brazil, and has a history of use in the treatment of multiple diseases, including heart disease, respiratory disorders, convulsion, intestinal disturbance and liver fatigue ( 6 ). Isoforskolin (ISOF) is the principle active component of C. forskohlii native to the southwest region of China, and has previously been studied for its anti-inflammatory effects ( 7 , 8 ). Notably, a study performed by Yang et al ( 9 ) observed that ISOF reduced the secretion of lipopolysaccharide (LPS)-induced cytokines, namely TNF-α, IL-1β, IL-6 and IL-8, in human mononuclear leukocytes.…”
Section: Introductionmentioning
confidence: 99%